Asthma - a healthcare, environment and green transformation - associated disease - Mazur, Sylwia; Dąbrowska, Natalia; Madera, Magdalena; Zdunek, Roksana; Marcinkowski, Krzysztof; Strus, Karolina; Kublińska, Aleksandra; Nagórska, Emilia (Quality in Sport, 2024)
Air pollution both anthropogenic and from natural sources impacts human health and is a rising problem for healthcare around the world. Key pollutants, such as particulate matter, carbon monoxide, ozone, nitrogen dioxide, and sulphur dioxide, contribute especially to respiratory illnesses. This review examines recent studies in the field of asthma and air pollution correlation, particularly mechanisms of air pollution-related damage, asthma symptoms exacerbations and the risk of developing the disease due to poor air quality. Studies show that pollutants affect the immune system by triggering pro-inflammatory responses and oxidative stress, particularly in individuals with asthma. The review present findings of exacerbation of asthma symptoms and increased frequency of asthma attacks along with higher rates of hospital admissions and emergency room visits due to exposure to common air pollutants. Additionally, prenatal and early-life exposure to traffic-related air pollution proved to significantly increase the risk of developing asthma in children. The review also critically identifies data gaps and methodological inconsistencies in some investigations. The complex relationship between air pollution and asthma is for sure an interesting field to explore furtherly. Analysed materials emphasize the critical need for global measures to reduce air pollution, including stricter air quality regulations and public awareness initiatives.